STRATEGI UMPAN BALIK LANGSUNG TERHADAP MAHASISWA; POTRET PADA KELAS MENULIS BAHASA ASING - Elyza, Ferlya; Sugirin, Sugirin; Triastuti, Anita; Meutia, Putri Dini (Wahana Literasi: Journal of Language, Literature, and Linguistics, 2023)
This study reports needs analysis results. It aims to analyze students' needs in an effort of developing the learning strategies of direct corrective feedback in an EFL Writing class context. The initial step is to investigate the needs of students in receiving feedback as well as teacher educators' strategies in providing feedback. 39 students and 3 teacher educators are involved in this study. They are from two private universities. The questionnaire, as the main instrument, is in a form of closed-ended for students and closed along with the open questionnaire for teacher educators. The result of the analysis indicates that feedback plays an important role in overcoming students' problems in writing. It reflects that students thoroughly need feedback, either in oral corrective feedback or written corrective feedback. Thus, it concludes that the need for effective feedback must be balanced by the students' efforts to respond to it as a form of the learning process. Both direct and indirect feedback is helpful for students either in oral or written form.